Effectiveness of interpersonal communication at Pelindo Multi Terminal Branch Makassar Sub holding office (Pinisi Journal of Officers Review, 2024)
Interpersonal relationships are formed when the process of processing messages gets feedback occurs, both verbal and nonverbal. As interpersonal relationships grow, interpersonal communication also occurs, which is a communication process that requires more than one person. This study aims to determine the effectiveness of interpersonal communication at the Pelindo Multi Terminal Branch Makassar Sub holding Office and to determine the supporting and inhibiting factors at the Pelindo Multi Terminal Branch Makassar Sub holding Office. This research approach is a qualitative research approach and a type of descriptive research, the informants in this study are the Deputy Branch Manager of Operations, HSSE Officer and Staff at the Makassar Sub holding Office of Pelindo Multi Terminal Branch. Data collection techniques carried out in this study used observation, interview and documentation methods. The data analysis techniques used are data condensation techniques, data presentation, conclusions, and verification. The results of this study show that all indicators used in the study of interpersonal communication effectiveness at the Pelindo Multi Terminal Branch Makassar Sub holding Office are classified as effective. The indicator in question is that openness is classified as effective because the delivery of information and messages will be conveyed in detail and maximize to convey directly. Empathy is classified as effective because of the caring attitude by providing a quick response and solutions presented. Support is classified as effective because of the support of all parties that can be felt and the holding of regular meetings to find out the obstacles felt and progress to be implemented. A positive attitude is classified as effective because leaders and employees show a positive behavioural attitude by listening and thinking about solutions to every problem faced and similarities are classified as effective because of the mutual respect that must be cultivated by both leaders and employees.